Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 10 - Radical Expressions and Equations - 10-4 Solving Radical Equations - Practice and Problem-Solving Exercises - Page 624: 34



Work Step by Step

$Given,$ $2y=\sqrt (5y+6)$ Squaring both sides,we get: $4y^{2}=5y+6$ $4y^{2}-5y-6=0$ $(4y+3)(y-2)=0$ $y=2,y=\frac{-3}{4}$ We need to check by the putting the obtained solutions in the original equation. $y=2$ $L.H.S=2X2=4$ $R.H.S=\sqrt (5X2+6)=\sqrt 16=4$ $L.H.S=R.H.S$,hence it is a valid solution $y=\frac{-3}{4}$ $L.H.S=2X\frac{-3}{4}=\frac{-3}{2}$ $R.H.S=\sqrt (5X\frac{-3}{4}+6)=\sqrt \frac{24-15}{4}=\sqrt\frac{9}{4}=\frac{3}{2}$ $L.H.S$ does not equal $R.H.S$,hence it is an extraneous solution.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.